Architectural Decisions for HW/SW Partitioning Based on Multiple Extra-Functional Properties - Sapienza, Gaetana; Crnkovic, Ivica; Potena, Pasqualina (2014 IEEE/IFIP Conference on Software Architecture, 2014)
Growing advances in hardware technologies are enabling significant improvements in application performance by the deployment of components to dedicated executable units. This is particularly valid for Cyber Physical Systems in which the applications are partitioned in HW and SW execution units. The growing complexity of such systems, and increasing requirements, both project- and product-related, makes the partitioning decision process complex. Although different approaches to this decision process have been proposed during recent decades, they lack the ability to provide relevant decisions based on a larger number of requirements and project/business constraints. A sound approach to this problem is taking into account all relevant requirements and constraints and their relations to the properties of the components deployed either as HW or SW units. A typical approach for managing a large number of criteria is a multicriteria decision analysis. This, in its turn, requires uniform definitions of component properties and their realization in respect to their HW/SW deployment. The aim of this paper is twofold: a) to provide an architectural metamodel of component-based applications with specifications of their properties with respect to their partitioning, and b) to categorize component properties in relation to HW/SW deployment. The metamodel enables the transition of system requirements to system and component properties. The categorization provides support for architectural decisions. It is demonstrated through a property guideline for the partitioning of the System Automation and Control domain. The guideline is based on interviews with practitioners and researchers, the experts in this domain.